Care in Sport Coaching Pedagogical Cases. - Cronin, Colum; Armour, Kathleen (Milton : Routledge, 2018)
While it is accepted that sport coaches should safeguard participants, Care in Sport Coaching: Pedagogical Cases argues that coaches have a duty of care that moves beyond protection and involves the development of caring relationships with athletes. Recent high-profile incidents of abuse in sport highlight the need to reposition coaching as a caring activity and to embed care within coach education and coaching policy. Based around extended case studies, this book provides grounded accounts of how coaches care in their everyday practice. These case studies are analysed using multidisciplinary theoretical perspectives to illustrate and problematise how coaches care. Conclusions are provided, based on these analyses, that will help coach educators, researchers and policy makers establish care as a key facet of everyday sport coaching activities. Additionally, the book offers guidelines that will aid practitioners to enact care in their practice. This is important reading for coaches, researchers, lecturers and students who are concerned with the role of coaches and the development of coaching practice.
Cover; Title; Copyright; Dedication; Contents; List of contributors; Acknowledgements; 1 Introduction to care in coaching; 2 Care theory and sport coaching; 3 Why pedagogical case studies?; 4 Nurturing care in sport coaching: Jane's story; 5 Caring through science and autonomy: Terry's story; 6 Caring for, and with, others: Julie's story; 7 The cost of caring: Dave's story; 8 Conclusions, guidelines and future questions; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.